Application of the Guided Inquiry Model to Improve Student's Motivation and Creativity - Murniati Murniati; Evendi Evendi; Rahma Dani (Jurnal Penelitian Pendidikan IPA, 2021)
The application of an attractive learning model is one of the things that affect students' motivation and creativity in learning. The review results so far show that learning activities are still using conventional learning models such as direct learning models. The purpose of this study was to determine the application of the guided inquiry learning model in increasing students' motivation and creativity on temperature and heat material at SMAN 4 Wira Bangsa Aceh Barat. The research method used was pre-experimental with one group pretest-posttest design. The instrument used in the study consisted of a questionnaire. The results showed that applying the guided inquiry learning model could increase students' motivation in the matter of temperature and heat. Increasing students' learning motivation can be seen from the average N-gain value of 0.6, including the medium category. The results of the average difference test obtained a significance value of 0.000 <0.05, meaning that there was a significant difference before and after applying the guided inquiry learning model. Then the results of the analysis of indicators on aspects of attention, relevance, confidence, and satisfaction obtained a score > 80 then included in excellent categories. The application of the guided inquiry learning model can increase students' creativity in the material of temperature and heat. Increasing students' creativity can be obtained an average N-gain value of 0.7, including the high category. The results of the average difference test got a significance value of 0.000 < 0.05, meaning that there was a significant difference before and after applying the guided inquiry learning model. The results of the analysis of indicators through the results of questionnaires and observations consisting of fluency, flexibility, and novelty obtained an average score of > 75, including the high category. The conclusion in this study proves that the guided inquiry model can increase students' motivation and creativity on temperature and temperature heat materials